Al-SyawÄÅ¼ al-Naá¸¥wiyyah wa al-á¹¢arfiyyah fi á¸¤Äsyiyah al-á¹¢abbÄn â€˜ala AsymÅ«nÄ« (DirÄsah Lugawiyyah Miâ€™yariyah) - Ali Burhan (Arabic Education Program IAIN Pekalongan, 2021)
Occasionally the number of fluent shahids cannot be the barometer in constructing rules of nahwu ṣarf rules, because of its characteristic as sima’i which cannot be practiced. Likewise, the form of syaż or anomaly that has been formulated by the experts is inversely proportional to the number of fluent texts as the main barometer of language rules. Therefore, this form can be accepted in the term of qiyasi and sima’i. This study aims to examine the anomalous methods in the book of Ḥasyiyah Sabban Syarḥ Asymuni from the perspective of prescriptive linguistics (manhaj mi'yari). The detailed explanation is presented in the form of a thematic study of nahwu ṣarf . The results showed that the justification of the nahwu sharf anomaly only focused on the syahīd /text whose source was unknown, enabling the consensus of nahwu scholars following Baṣrah mażhab. The form of the anomaly reinforced by the fluent syahīd is not the same degree. This rule is not anomalous because it comes from an eloquent source, but it should not be used as a standard in formulating rules because there is no general qiyas.